CHILDHOOD NEGLECT AND OBSESSION: A PSYCHOANALYTIC LENS ON THE ROCKING HORSE WINNER BY D.H LAWRENCE - Ali, Muhammad Ilham (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
The short story